Catalytically induced nanographitic phase by a platinum-ion implantation/annealing process to improve the field electron emission properties of ultrananocrystalline diamond films. Issue 11 (21st March 2015) - Sankaran, Kamatchi Jothiramalingam; Kalpataru, Panda; Balakrishnan, Sundaravel; Tai, Nyan-Hwa; Lin, I.-Nan
<x xml:space="preserve">Abstract</x> Pt nanoparticles catalytically induce nanographitic phases in grain boundaries achieving highly conducting ultrananocrystalline diamond films with enhanced EFE properties.